Que cousa he virgula?: changes in the comma functional usage in grammar rules from the 17th to the 19th centuries - Rodrigues, Aline de Azevedo [UNESP]; Goncalves, Maria Filomena (Univ Fed Rio De Janeiro, Fac Letras, 2020)
The purpose of this paper is to investigate aspects of the historical development of punctuation and writing systems. For this, we focus on different comma functions observed in Portuguese grammar prescriptions published from the 17th to the 19th centuries, which we interpret as an effect of different conceptions of language, of punctuation and of relation among speech and writing. Our assumption is that the complex functioning of punctuation seems to be a constitutive feature of the system because of its heterogeneous history. Based on the results, we found a functioning change over the centuries, suggesting a coexistence of several functions, fact that corroborates a theory that considers punctuation marks as evidences of the multidimensional nature of language.
Keywords: Writing; Punctuation; Portuguese; Comma; Language Change